Reconceptualizing Problem-Based Learning for Transformative Learning: A Qualitative Study in Higher Education - Farisha Andi Baso; Eka Prabawati Rum; Ratu Yulianti Natsir; Markus Deli Girik Allo (Universitas Sulawesi Barat, 2026)
This study examines the enhancement of the Problem-Based Learning (PBL) method to facilitate transformative learning in higher education students. PBL is esteemed for its capacity to improve critical thinking and problem-solving skills. Transformative learning theory emphasizes critical reflection and viewpoint transformation, providing a foundation for reconceptualizing PBL as an approach that enhances cognitive skills while also altering learners’ worldviews. A qualitative approach was utilized, directed by two research inquiries: 1. What is the learners' experience of the flipped problem-based learning method in promoting transformative learning? 2. What aspects of the PBL approach most significantly facilitate the transformation of learners' perspectives? Data were gathered from 15 university students via semi-structured interviews and focus group discussions. Thematic analysis was employed to understand the data. The findings identified four principal themes: (1) the confrontation of disorienting dilemmas, (2) critical reflection, (3) dialogic collaboration and peer influence, and (4) alterations in self-perception and learning orientation. The study indicates that intentional redesign of PBL with authentic challenges, systematic reflection, and peer dialogue transcends procedural problem-solving, promoting transformative learning. The findings underscore the significance for educators, curriculum developers, and institutions, stressing the necessity of incorporating transformative learning principles into project-based learning practices.